Preoperative abdominal straining in uncomplicated stress urinary incontinence: is there a correlation with voiding dysfunction and de novo overactive bladder after mid-urethral sling procedures?. (November 2021) - Lacovelli, Valerio; Serati, Maurizio; Bianchi, Daniele; Braga, Andrea; Turbanti, Andrea; Agrò, Enrico Finazzi
Objectives: To evaluate the role of preoperative abdominal straining in predicting de novo overactive bladder (OAB) and voiding dysfunction in female patients undergoing suburethral taping by trans-obturator approach (TVT-O) for uncomplicated stress urinary incontinence (SUI). Methods: Data from patients who underwent TVT-O surgery for SUI were retrospectively analyzed. Inclusion criteria included: history of pure SUI. Exclusion criteria included previous surgery for urinary incontinence, pelvic radiation, pelvic surgery within the last 3 months, and anterior or apical pelvic organ prolapse (POP) ⩾ +1 cm. Voiding dysfunction has been defined through symptoms and or urodynamics (UDS) signs. Accordingly, patients were divided into group A and group B according to the presence of abdominal straining during UDS. Patients were observed clinically and with UDS at a 3-year follow-up. Results: A total of 192 patients underwent TVT-O surgery for uncomplicated SUI. Preoperative abdominal straining was identified in 60/192 patients (Group A: 31.2% vs Group B: 68.8%). Qmax was not different in the two groups (Group A: 19.5 vs Group B: 20.5 mL/s, p  = 0.76). Demographics was similar for the two groups regarding age, parity. At 3-year follow-up, voiding dysfunction was reported in Group A: 9 and Group B: 8 patients ( p  = 0.056), de novo OAB was significantly reported in Group A: 23 and Group B: 26 patients ( p  = 0.007). Conclusion: Preoperative abdominal straining was found to be related to a significant incidence of de novo OAB. A significant correlation was not assessed for postoperative voiding dysfunction. Further studies may better define the impact of preoperative abdominal straining.